Factors Associated with Autism Early Detection to Minimize the Need for Long-Term Care in Children: A Cross-Sectional Study - I Gusti Ngurah Made Kusuma Negara; Siti Komariyah; Ni Made Sri Rahyanti; Anak Agung Istri Wulan Krisnandari D (Journal Of Nursing Practice, 2025)
Background: Autism is characterized by a total withdrawal from the outside world and a complete lack of interaction with the outside world. It is a complex developmental disorder affecting behavior, resulting in deficits in communication skills, social relationships, and emotional relationships with others. Symptoms are evident before the child is three years old. Autism has been increasingly reported in recent years. However, in Indonesia, some children are still diagnosed with autism late.Purpose: This study aimed to determine factors influencing the early detection of autism.Methods: This study used a cross-sectional correlation study. The study population was parents of children with autism registered at the Bali Province Special Needs School (SLB), with a sample size of 81. Data analysis used univariate analysis (percentages and frequencies) and bivariate analysis (Chi-square test). Results: The study showed that the majority of respondents had primary/secondary education (66.7%), the majority were unemployed (55.6%), the majority had conducted regular and proper child development monitoring (82.7%), and the majority of children had received early detection for autism (53.1%). The correlation test results showed a relationship between parental education (p = 0.028), parental occupation (p = 0.028), and the number of children (p = 0.011) with early detection of autism in children.Conclusion: ore than half of the children had received early detection for autism. Early detection needs to be further enhanced through effective education about the importance of early detection for children.